Hukum Perkawinan Islam Dalam Kuasa Pemilik Modal - Zayad Abd. Rahman (Realita: Jurnal Penelitian dan Kebudayaan Islam, 2015)
Islamic marriage law that grows and develops in the social space describing the multiple possibilities to beÂ interpreted through history. Issues around issues of justice, equality became the main centrum discussed withÂ different approaches. Thesis William Montgomery Watt states that the trade of Mecca is an important factorÂ for the emergence of Islam. Socioeconomic standpoint this has enriched the interpretation of the history ofÂ the emergence of Islam as a debatable academically. Although theses Watt also received sharp criticism fromÂ Patricia Crone, but both are at the same point the assumption that Mecca declared as an important tradingÂ town in the 7th century AD.